The new girl - Calin, Cassandra, 1994- (New York, NY : Graphix, an imprint of Scholastic, 2024)
Leaving Romania, the only home she's ever known, Lia is thrust into a world where everything is different and with so many changes happening at once, including a new school and unpleasant periods, she wonders if she'll ever feel like herself again.
School Library Journal starred, June 2024
3-6
GN210L
Keywords: Menstruation -- Comic books, strips, etc; Menstruation -- Juvenile fiction; Immigrants -- Comic books, strips, etc; Immigrants -- Juvenile fiction; Identity (Philosophical concept) -- Comic books, strips, etc; Identity (Philosophical concept) -- Juvenile fiction; Schools -- Comic books, strips, etc; Schools -- Juvenile fiction; Menstruation -- Fiction; Immigrants -- Fiction; Identity -- Fiction; Schools -- Fiction; School comics; Graphic novels; Comics (Graphic works); Coming-of-age comics